Multipotent adult progenitor cells for hypoxic-ischemic injury in the preterm brain. Issue 1 (December 2015) - Jellema, Reint; Ophelders, Daan; Zwanenburg, Alex; Nikiforou, Maria; Delhaas, Tammo; Andriessen, Peter; Mays, Robert; Deans, Robert; Germeraad, Wilfred; Wolfs, Tim; Kramer, Boris
Abstract Background Preterm infants are at risk for hypoxic-ischemic encephalopathy. No therapy exists to treat this brain injury and subsequent long-term sequelae. We have previously shown in a well-established pre-clinical model of global hypoxia-ischemia (HI) that mesenchymal stem cells are a promising candidate for the treatment of hypoxic-ischemic brain injury. In the current study, we investigated the neuroprotective capacity of multipotent adult progenitor cells (MAPC® ), which are adherent bone marrow-derived cells of an earlier developmental stage than mesenchymal stem cells and exhibiting more potent anti-inflammatory and regenerative properties. Methods Instrumented preterm sheep fetuses were subjected to global hypoxia-ischemia by 25 min of umbilical cord occlusion at a gestational age of 106 (term ~147) days. During a 7-day reperfusion period, vital parameters (e.g., blood pressure and heart rate; baroreceptor reflex) and (amplitude-integrated) electroencephalogram were recorded. At the end of the experiment, the preterm brain was studied by histology. Results Systemic administration of MAPC therapy reduced the number and duration of seizures and prevented decrease in baroreflex sensitivity after global HI. In addition, MAPC cells prevented HI-induced microglial proliferation in the preterm brain. These anti-inflammatory effects were associated with MAPC-induced prevention of hypomyelination after global HI. Besides attenuation of the cerebral inflammatory response, our findings showed that MAPC cells modulated the peripheral splenic inflammatory response, which has been implicated in the etiology of hypoxic-ischemic injury in the preterm brain. Conclusions In a pre-clinical animal model MAPC cell therapy improved the functional and structural outcome of the preterm brain after global HI. Future studies should establish the mechanism and long-term therapeutic effects of neuroprotection established by MAPC cells in the developing preterm brain exposed to HI. Our study may form the basis for future clinical trials, which will evaluate whether MAPC therapy is capable of reducing neurological sequelae in preterm infants with hypoxic-ischemic encephalopathy.